Protocol paper: Multi-site, cluster-randomized clinical trial for optimizing functional outcomes of older cancer survivors after chemotherapy. Issue 6 (July 2022) - Yilmaz, S.; Janelsins, M.C.; Flannery, M.; Culakova, E.; Wells, M.; Lin, P.-J.; Loh, K.P.; Epstein, R.; Kamen, C.; Kleckner, A.S.; Norton, S.A.; Plumb, S.; et al.
Abstract: Background: Cancer survivors over the age of 65 have unique needs due to the higher prevalence of functional and cognitive impairment, comorbidities, geriatric syndromes, and greater need for social support after chemotherapy. In this study, we will evaluate whether a Geriatric Evaluation and Management-Survivorship (GEMS) intervention improves functional outcomes important to older cancer survivors following chemotherapy. Methods: A cluster-randomized trial will be conducted in approximately 30 community oncology practices affiliated with the University of Rochester Cancer Center (URCC) National Cancer Institute Community Oncology Research Program (NCORP) Research Base. Participating sites will be randomized to the GEMS intervention, which includes Advanced Practice Practitioner (APP)-directed geriatric evaluation and management (GEM), and Survivorship Health Education (SHE) that is combined with Exercise for Cancer Patients (EXCAP©®), or usual care. Cancer survivors will be recruited from community oncology practices (of participating oncology physicians and APPs) after the enrolled clinicians have consented and completed a baseline survey. We will enroll 780 cancer survivors aged 65 years and older who have completed curative-intent chemotherapy for a solid tumor malignancy within four weeks of study enrollment. Cancer survivors will be asked to choose one caregiver to also participate for a total up to 780 caregivers. The primary aim is to compare the effectiveness of GEMS for improving patient-reported physical function at six months. The secondary aim is to compare effectiveness of GEMS for improving patient-reported cognitive function at six months. Tertiary aims include comparing the effectiveness of GEMS for improving: 1) Patient-reported physical function at twelve months; 2) objectively assessed physical function at six and twelve months; and 3) patient-reported cognitive function at twelve months and objectively assessed cognitive function at six and twelve months. Exploratory health care aims include: 1) Survivor satisfaction with care, 2) APP communication with primary care physicians (PCPs), 3) completion of referral appointments, and 4) hospitalizations at six and twelve months. Exploratory caregiver aims include: 1) Caregiver distress; 2) caregiver quality of life; 3) caregiver burden; and 4) satisfaction with patient care at six and twelve months. Discussion: If successful, GEMS would be an option for a standardized APP-led survivorship care intervention. Trial Registration: ClinicalTrials.gov NCT05006482, registered on August 9, 2021.